Morphological characterization and genetic barcoding of kuttiatoor mango accessions - M R Dinesh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
A survey conducted during 2013-14 to collect and characterize the Kuttiattoor mango accessions from Kerala, revealed large unique variability in morphological, biochemical and DNA barcode data. All the accessions were polyembryonic with fruit maturity during February-March. The mature fruit length (cm), width (cm) and leaf length (cm) ranged from 5.10 – 9.60 (cm), 4.60 – 8.40 (cm) and 12.47- 30.40 (cm) respectively.